Objektivizace poranĕní hrudníku a s nimi sdruzených poranĕní pomocí Abbreviated Injury Scale a New Injury Severity Score - Adámek, T; Vajtr, D; Stefan, J (Soudni lekarstvi, 2001)
The authors focused attention on objectivization of the severity of chest injuries and associated injuries using the Abbreviated Injury Scale (AIS) and the New Injury Severity Score (NISS). They evaluated injuries detected on post-mortem examination in subjects who died from the sequelae of injuries in the Faculty Hospital Prague 10. The group comprised a total of 90 subjects regardless of sex aged 17-94 years who died in the hospital in 1996-2000. Traffic injuries accounted for 70% deaths, other blunt injuries for 27.8% and only 2.2% were penetrating injuries of the chest. The mean AIS value of the chest was 3.7, the mean value of NISS was 50.7. The NISS value declined in relation to age of the deceased patients and the period of survival. The period of survival varied from 30 mins. to 136 days. The mean NISS value on survival up to 5 hours after injury was 55.0. On comparison of our group we found that the results were consistent with those of American studies.
Keywords: Adolescent; polytrauma; senioři; zkrácená stupnice závažnosti úrazů; Thoracic Injuries; skóre závažnosti úrazu; Aged; Middle Aged; Abbreviated Injury Scale; poranění hrudníku; Adult; Forensic Medicine; Multiple Trauma; senioři nad 80 let; mladiství; soudní lékařství; dospělí; lidé středního věku; Injury Severity Score; Aged, 80 and over; lidé; Humans; pitva; Autopsy